Folic acid modulates cancer‐associated micro RNAs and inflammatory mediators in neoplastic and non‐neoplastic colonic cells in a different way. Issue 12 (9th November 2017) - Niemann, Birgit; Nemitz, Anke; Werner, Josephine; Mai, Ha Dong; Steinberg, Pablo; Lampen, Alfonso; Ehlers, Anke
Abstract : Scope: Scientific evidence suggests that folic acid (FA) supplementation protects the healthy colonic mucosa from neoplastic transformation but may promote the progression of precancerous lesions. The underlying molecular mechanisms are not fully understood. Therefore, we explored, if high physiological FA doses provoke changes in (i) promoter‐specific DNA methylation (ii) expression of cancer‐associated micro RNAs (miRNAs) and (iii) inflammatory mediators in human neoplastic and non‐neoplastic colonic cell lines. Methods and results: The malignant and the non‐malignant colonic cell lines HT29 and HCEC were adapted to different near‐physiological FA concentrations. Using DNA methylation and pathway specific PCR arrays, high‐physiological FA concentrations revealed no relevant impact on promoter methylation but a number of differences between the cell lines in the expression of miRNAs and inflammatory mediators. In the HCEC cell line pro‐inflammatory genes were repressed and the miRNA expression remained nearly unaffected. In contrast, in the HT29 cell line tumour‐suppressive miRNAs were predominantly down‐regulated and the expression of genes involved in chemotaxis and immunity were modulated. Conclusion: The different effects of high‐physiological FA concentrations in malignant and non‐malignant colonic cell lines regarding cancer‐associated miRNAs and inflammatory mediators may contribute to the different effects of FA supplementation on colonic carcinogenesis. Abstract : Folic acid generates cells an anti‐inflammatory microenvironment in normal colonic epithelial by down‐regulating inflammatory features and up‐regulating the cytokine IL18, which is involved in maintaining the healthy intestinal barrier function. In contrast, folic acid generates in colon cancer cells an inflammatory and tumour promoting microenvironment by supporting aberrant micro RNA expression, enhancing the TNFα triggered NFκB activation, up‐regulating the CXCR4 receptor and dysregulating the leucocyte‐attracting chemokines CSF1, CCL5 and CXCL6 as well as the toll‐like receptors TLR3 and TLR4 along with their downstream AP1‐transcription factor unit FOS. All regulated molecules are engaged in the crosstalk of tumour cells with macrophages, neutrophils and other cells at the tumour environment interface.